Effect of Sex on Recovery From Persistent Postconcussion Symptoms in Children and Adolescents Participating in an Active Rehabilitation Intervention. Issue 2 (March 2019) - Gauvin-Lepage, Jérôme; Friedman, Debbie; Grilli, Lisa; Gagnon, Isabelle
Abstract : Objective: To estimate the extent to which biologic sex contributes to the severity of postconcussion symptoms (PCSs) in concussed youth, who are slow to recover and who receive an active rehabilitation intervention (ARI) as part of their standard care. Setting: The concussion clinic of a pediatric trauma center in Canada. Participants: A total of 355 youth with persistent PCS (188 girls and 167 boys) as per the following criteria: (1) diagnosed with a concussion (or mild traumatic brain injury) as per the 2004 World Health Organization definition; (2) aged 8 to 17 years (mean = 14.34, standard deviation [SD] = 2.22 years); (3) presenting with at least 1 PCS interfering with daily activities (mean total PCS score at initial assessment = 24.50, SD = 18.88); and (4) on ARI 4 weeks postinjury (mean = 30.46, SD = 3.74 days). Design: A retrospective analysis of a prospective cohort. Main Measures: PCS severity, measured by the PCS Scale (PCSS) included in the Sports Concussion Assessment Tool-3, was the dependent variable. PCSs were assessed 3 times over a 4-week period. Results: Boys presented with significantly fewer symptoms than girls 4 weeks postinjury, at initiation of the ARI (PCSS total score mean: ♂ = 19.9, ♀ = 28.5, P < .001, confidence interval = −14.8 to −6.4), at 2 and 4 weeks of follow-up, but the rate of recovery was slightly faster for girls over the follow-up period. Conclusion: Despite differences between the PCSS score reduction after 4 weeks of intervention, our results favored to a slightly faster recovery for girls over the follow-up period. Although our findings are not strong enough to suggest distinct sex-specific intervention, both boys and girls benefit from participating in an ARI.